Water and its partially dissociated fragments at metal surfaces. Issue 1 (6th February 2017) - McBride, F.; Hodgson, A.
Abstract: Water and its fragments are present on metal surfaces under all but the most extreme conditions, acting both as a reactive species and as a ligand in ways that have yet to be fully explored. This review focuses on experimental studies of the chemical species and hydrogen bonding structures that form in the first layer adsorbed on a metal surface. The development of non-invasive probes that avoid dissociating water, or disrupting fragile bonding structures, now allows experiments to distinguish between different structural models for water and its fragments at the surface, allowing us to test the accuracy of modern structural calculations and provide a better picture of how the metal surface influences the structures and chemical species present. We start by describing the behaviour of Pt(1 1 1), whose redox chemistry is important in electrochemical fuel cells and has been studied in detail, providing a good reference system against which to discuss the effect changing the surface symmetry and metal reactivity has on the interface structure. Evidence for the presence and the role of hydroxyl and hydrated 'hydronium' species is described and we discuss the outlook for future experiments and identify some questions that remain to be resolved.